2005
DOI: 10.1071/bt04034
|View full text |Cite
|
Sign up to set email alerts
|

Grass-tree (Xanthorrhoea semiplana, Liliaceae) facilitation of the endangered pink-lipped spider orchid (Caladenia syn. Arachnorchis behrii, Orchidaceae) varies in South Australia

Abstract: We examined the role of the grass-tree Xanthorrhoea semiplana F.Muell. canopy in the survival of the nationally endangered orchid Caladenia (syn. Arachnorchis) behrii Schltdl. at three sites in the northern Adelaide region. We compared grazing and pollination of the flowering orchids within and away from the grass-tree canopy. Grass-trees generally provided significant protection from grazing, but orchids protected by grass-trees experienced reduced pollination for 2 out of 5 years. The net effect of these int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Sudden decline of local populations can occur in habitats which are in good condition. Grazing animals such as kangaroos observed in other studies [56,57] were rare at the study site. However, suspected symptoms of virus infection were sometimes observed before plants disappeared.…”
Section: Climate and Habitat Conditionsmentioning
confidence: 73%
“…Sudden decline of local populations can occur in habitats which are in good condition. Grazing animals such as kangaroos observed in other studies [56,57] were rare at the study site. However, suspected symptoms of virus infection were sometimes observed before plants disappeared.…”
Section: Climate and Habitat Conditionsmentioning
confidence: 73%
“…Over half (61 of 107) of the species analysed had a significant ( P < 0.05) indicator value for a particular community, indicating that the classification encompassed a large proportion of variation in the vegetation. A number of the species with high indicator values are of particular interest to management, including species of Xanthorrhoea , which provide key habitat to plants and animals (Petit & Dickson ; Frazer & Petit ; Swinburn et al. ) and Leptospermum continentale and Pteridium esculentum , which are important fire fuel elements (McCarthy et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although this tentative model is yet to be tested, it is interesting to consider the underlying mechanisms. Petit and Dickson (2005) found that the pollination rate of a sexually-deceptive orchid decreased as the amount of vegetation within close proximity increased, which they attributed to increased difficulty for pollinators in locating orchid flowers. In the heathy woodland system studied in the present paper, vegetation structure is low in the early post-fire environment, gradually increasing to a maximum in mid successional stages, and then declining again late in succession (Cheal 2010;Brown 2013).…”
Section: Discussionmentioning
confidence: 99%